A Comparative Analysis of Public Relations Curricula: Does It Matter Where You Go to School, and Is Academia Meeting the Needs of the Practice?. (March 2016) - Auger, Giselle A.; Cho, Moonhee
According to scholars, there has been a move toward a more professional or occupational focus in postsecondary education, a focus that Grubb and Lazerson suggest "undermines education's moral, civic, and intellectual purposes." 1 The purpose of this study was to evaluate the public relations curricula of U.S. universities and colleges and the requirements for entry into the profession. Results indicated that while there are differences, public relations curricula appear to be equally strong regardless of department or type of institution in which the program is located. Moreover, results indicated that the public relations curricula appear to meet the needs of the practice and that the perceived gap between offering of social media courses and the needs of practice may be temporary and illusionary.